Reimagining social movements : from collectives to individuals - Farro, Antimo, 1951-; Lustiger-Thaler, Henri, 1951- (Global connections (Ashgate (Firm)), 2014)
The social scientific study of social movements remains largely shaped by categories, concepts and debates that emerged in North Atlantic societies in the late 1960s and early 1970s, namely resource mobilization, framing, collective identity, and new social movements. It is now, however, increasingly clear that we are experiencing a profound period of social transformation associated with online interactivity, informationalization and globalization. This book explores emerging forms of movement and action not only in terms of the industrialized countries of the North Atlantic, but recognize th.